Business flies: The trade promoting effect of air connectivity - Feicheng Wang; Zheng Wang; Zhou Zhou (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
Despite the increasing dominance of digital technology in modern communications, face-to-face interactions are believed to play an irreplaceable role in facilitating complex crossborder business transactions. However, empirical research to identify the impact often faces the challenge of two-way causality when cross-country in-person meetings are measured by international air passenger flows. We propose a novel instrumental variable to estimate the causal effect of international air travel on bilateral trade. Our identification strategy exploits variations in connecting flight capacities in the global flight network to leverage exogenous variations in the air connectivity between two countries. With the inclusion of stringent fixed effects in our estimations and checked for robustness against many possible threats to the identification, our results show that international air connectivity facilitates trade between countries, but only for industries with a higher reliance on relationship-specific investments or incomplete contracts. We also find that stronger enforcement of contracts in the importing country amplifies the trade promoting effect of air connectivity, and that trade in new products, relative to existing products, responds more positively to improved air transport links. Together, these findings suggest that in-person communications reduce transaction costs in international trade by facilitating the exchange of complex knowledge that cannot be easily and completely codified and by breaking market entry barriers.
Keywords: F1; F2; R4; 330; air connectivity; face-to-face communications; connecting flights; trade